2018
DOI: 10.1515/jomb-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone as a Diagnostic Marker in Egyptian Infertile Polycystic Ovary Syndrome Females: Correlations with Vitamin D, Total Testosterone, Dyslipidemia and Anthropometric Parameters

Abstract: SummaryBackgroundRecent studies have highlighted the role of anti-Müllerian hormone (AMH) in numerous ovarian disorders. Polycystic Ovary Syndrome (PCOS) is one of the major causes of infertility in Egypt. Several reports have linked PCOS with vitamin D deficiency. This investigation illustrates the possibility of using serum AMH for PCOS diagnosis in infertile Egyptian females, determines the variables affecting it and correlates it with serum 25(OH)D, testosterone, dyslipidemia and anthropometric parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
5
23
0
1
Order By: Relevance
“…The current systematic review included eighteen cross-sectional studies and six interventional studies assessing the relationship between serum vitamin D levels and serum AMH levels. The cross-sectional studies demonstrated conflicting results, with several studies finding a positive correlation between serum AMH and vitamin D levels [42,46,50,61], while most studies reported largely negative findings [43][44][45]47,49,[51][52][53][54][55][56][57][58][59]. The systematic review and meta-analysis of the interventional studies revealed that vitamin D supplementations affect serum AMH levels but have opposite effects depending on the ovulatory statuses of the women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current systematic review included eighteen cross-sectional studies and six interventional studies assessing the relationship between serum vitamin D levels and serum AMH levels. The cross-sectional studies demonstrated conflicting results, with several studies finding a positive correlation between serum AMH and vitamin D levels [42,46,50,61], while most studies reported largely negative findings [43][44][45]47,49,[51][52][53][54][55][56][57][58][59]. The systematic review and meta-analysis of the interventional studies revealed that vitamin D supplementations affect serum AMH levels but have opposite effects depending on the ovulatory statuses of the women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Bednarska-Czerwińska et al [58] reported a negative correlation between AMH and vitamin D concentrations of up to approximately 30 ng/mL, while beyond that concentration, the trend became positive but statistically insignificant. In addition, differences in the population size may also account for negative findings, as some of the studies had small numbers of patients [43,49,[51][52][53][54]56,58] and were not adequately powered to detect small but significant associations between vitamin D and AMH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic Ovary Syndrome (PCOS) is the most abundant endocrine disorder in females of reproductive age and one of the main causes of infertility with a prevalence of 9–18 % worldwide (1). Reports state that PCOS constitutes a major health issue in Egyptian females (2, 3). According to the Rotterdam consensus in 2003, PCOS can be diagnosed by the occurrence of two of the following criteria: Oligo-and/or anovulation, clinical and/or biochemical features of hyperandrogenism, and polycystic ovaries on performing ultrasound investigations (4).…”
Section: Introductionmentioning
confidence: 99%
“…The INSR gene is located on chromosome 19 and it consists of 22 exons and 21 introns. The exons 17-21 encode the tyrosine kinase domain of the receptor, which is necessary for insulin signal transduction (16). Mutations in these exons can cause insulin resistance and hyperinsulinemia (17,18).…”
Section: Introductionmentioning
confidence: 99%